The Role of Influencer Marketing, Online Customer Reviews, and Brand Image in Forming purchase Decisions for Daviena Skincare on TikTok - sugeng purwanto; Rofi’atul Fadhiilah Rofi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study is directed to examine the influence of modern marketing factors, which include influencer marketing strategies, online reviews, and brand image in the consumer decision-making process on the purchase of Daviena Skincare  products through the social media platform TikTok. This study uses survey methods in a quantitative approach. The research subjects involved as many as 130 respondents who had experience buying Daviena products, so it was considered relevant to be used as a research sample through TikTok with purposive sampling techniques. The research data was obtained through the distribution of questionnaires and analyzed using the Partial Least Square (PLS) approach. The results of the study indicate that influencer marketing, online customer reviews, and brand image have a positive influence on purchasing decisions. This fact shows how essential it is to implement a digital marketing strategy that focuses on the use of social media as the main means of reaching consumers that involves collaboration with influencers and the use of consumer reviews, as well as a strong brand image that can improve consumer purchase decisions.